DENTAL AGE ESTIMATION FROM TOOTH DEVELOPMENT: A LITERATURE REVIEW - Nur Azizah, Anna; Dedek Yunus, Aditia; Puspitawati, Ria; Soedarsono, Nurtami; Winoto Suhartono, A. (Fakultas Kedokteran Gigi Unjani, 2024)
Age estimation is among several standard methods for identifying unknown individuals in disasters, accidents, crime victims, and identity forgery. Age estimation can be done through observation of the growth and development of dentition. Similar to fingerprints, teeth are unique and specific for each individual. This article discusses the methods of age estimation based on observation of dentition's growth and development process. Demirjian, Gustafson, Kvaal, Gleiser and Hunt, Schour and Massler, and Cameriere are the most commonly used age estimation methods. Each method has its challenges and limitations. Therefore, applying more than one method or conducting a repetition of measurement and calculation could improve the accuracy of the estimation. However, the influence of factors like heredity, ethnicity, and genetic tendencies in a particular population should also be considered. DOI : 10.54052/jhds.v3n3.p249-262